NON-CARCINOGENIC RISK TO THE HEALTH OF THE POPULATION OF AN INDUSTRIAL CITY FROM THE INFLUENCE OF ATMOSPHERIC EMISSIONS FROM AN ALUMINUM PLANT - Вера Викторовна Кислицына; Дмитрий Вячеславович Суржиков; Роман Анатольевич Голиков; Юлия Сергеевна Ликонцева (Медицина в Кузбассе)
The study aim was to assess and analyze the non-carcinogenic risk to the health of the population of the city of Novokuznetsk from the influence of atmospheric emissions from the aluminum smelter.